2011
DOI: 10.1371/journal.pgen.1002236
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Map of Mobile Element Insertion Polymorphisms in Humans

Abstract: As a consequence of the accumulation of insertion events over evolutionary time, mobile elements now comprise nearly half of the human genome. The Alu, L1, and SVA mobile element families are still duplicating, generating variation between individual genomes. Mobile element insertions (MEI) have been identified as causes for genetic diseases, including hemophilia, neurofibromatosis, and various cancers. Here we present a comprehensive map of 7,380 MEI polymorphisms from the 1000 Genomes Project whole-genome se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
381
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(423 citation statements)
references
References 72 publications
29
381
0
Order By: Relevance
“…These studies have also demonstrated that several types of epithelial cancers acquire somatic insertions of LINE-1 as they develop (15,19,24,26). Recent projects mining whole-genome sequencing data have extended our understanding of the scope of heritable LINE-1 insertions (20,21,47) and somatic retrotransposition (22,23,48) greatly.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies have also demonstrated that several types of epithelial cancers acquire somatic insertions of LINE-1 as they develop (15,19,24,26). Recent projects mining whole-genome sequencing data have extended our understanding of the scope of heritable LINE-1 insertions (20,21,47) and somatic retrotransposition (22,23,48) greatly.…”
Section: Discussionmentioning
confidence: 98%
“…Because of these barriers, and assumptions that interspersed repeats are not functional, characterizations of these sequences have been incomplete. Recently, however, strategies for mapping these elements have been developed based on selective PCR amplification (15)(16)(17), hybridizationbased enrichment (18,19), and read selection from wholegenome sequencing data (20)(21)(22). These studies underscore the continued activity of LINE-1 in modern humans, and demonstrated somatic insertions in several types of human malignancy (15,19,(22)(23)(24)(25)(26)(27).…”
Section: Significancementioning
confidence: 99%
“…[5][6][7][8][9][10] Although we cannot completely rule out the possibility of two independent two-step events, we suggest that both aberrations can be traced back to a shared primary Alu retrotransposition event. This interpretation is based on (i) identity of the region harboring the presumed integration; (ii) involvement of AluYb8 as one of the most active Alu subfamilies; 16 (iii) presence of a classical L1-endonuclease site; 16 (iv) the sequence representing the potential target site duplication to be of the typical size of 16 bp; 16 and (v) the rarity of the haplotype on which both variants reside. The fact that previous genome-wide studies did not identify the corresponding polymorphic Alu insertion 17 may be explained by the high genomic instability (mediation of two different deletions!)…”
Section: Discussionmentioning
confidence: 99%
“…or various L1 publications. Studies of L1s in the whole genome sequencing data of phase 1 of the 1000 genomes project have been published (Ewing & Kazazian, 2011; Stewart et al., 2011), and the L1s detected in these publications were annotated as known non‐reference L1s at the time of our L1‐seq analyses. Subsequently, in response to reviewer comments, we cross‐referenced our list of detected L1s with the 2015 publication on structural variants in the 1000 genomes project (Sudmant et al., 2015).…”
Section: Resultsmentioning
confidence: 99%